A rare complication of suprapubic catheterisation following pelvic reconstructive surgery for urinary incontinence. (7th September 2012) - Liang, Tina; Lazare, Darren; Schulz, Jane; Flood, Cathy
Abstract : Suprapubic (SP) catheterisation is commonly used for drainage of the bladder following pelvic surgery. Although it is a widely employed procedure, it is not without complications, such as infection and blockage. The authors report a rare complication of SP catheterisation involving a persistent SP catheter site fistulous tract and an infected haematoma significantly complicating a patient's postoperative course. Wound debridement, bladder drainage and a prolonged course of antibiotics were employed to successfully treat this complication. The exact mechanism of her complication is only speculative, however to our knowledge no similar cases of a fistula after removal of a SP catheter used for short-term bladder drainage have been reported.